(untitled) (Research Journal of Padmakanya Multiple Campus, 2023)
Accepting homosexuality is increasing in Nepali society, yet negative attitude toward homosexuals persists. In educational setting, homosexual students face direct or indirect discrimination. This article reports on the study aimed to assess the attitude of college students toward homosexuals in relation to various factors affecting it. A descriptive study was done on 160 students of Padmakanya Multiple Campus and Shanker Dev Campus using homophobia scale, a self-administered questionnaire that measured the affective, cognitive and behavioral aspects of homophobia. It was hypothesized that there would be difference in attitude toward homosexuals with regards to the independent variables used under the study. Exactly how these factors play role to form a college students’ overall attitude toward homosexuals is not fully understood, though associations between sex, religion and contact experience have been recognized. The study results show that male students and those who have no or negative contact experience with homosexuals hold more negative attitude than female students and those having homosexual friends. The implication of the study includes taking gender into account when working with issues surrounding homosexuality and emphasizing on more positive contact environments between heterosexual and homosexual students.